Analysis of the Urban Water Requisition Demand for the Purpose of Re-engineering and Water Network Optimization (Case Study: Tabriz' Eram Urban Area) - Aida Bagheri Basmenji; Alireza Mojtahedi; Aliyeh Rezayi (Salehan Institute of Higher Education, 2017)
Water shortage is one of the most important challenges of this century and it would be a serious obstacle for the mankind. In the near future, drinking water supply and water resources management will be at the forefront of planning for urban managers, which is becoming a crisis due to the serious shortage of water resources. This problem is more critical in country of Iran, where water depletion is now receiving serious attention. Different water management programs have been started by government to conserve and manage water more efficiently, especially in some critical areas such as Tabriz megacity located in North East of the country. Eram town is one of the problematic areas of Tabriz. Hence, in this study, we tried to do reengineering for this town to offer some solutions for the problems related with water supplying of the implemented network in this region. Regarding this issue, the GIS (Geographic information system) data of the available water supply network was used and the collected field data such as consumption rates in current conditions were applied to the network. Then the calibration of model was performed. Eram Town water distribution network reengineering has been performed considering a 2043 plan, taking into account population growth and the increase in consumption. In conclusion, it is suggested that, the network will perform more efficiently by adding new pipes or modifying the existing pipes. Also, the problem of lack of pressure in some parts of the network which cannot fulfill the requirements of subscribers at peak water usage hours, could be solved.